Case Report: Primary adrenal insufficiency due to bilateral adrenal infarction and antiphospholipid syndrome in Covid19 - A complicate case of cardiogenic shock - Fischetti, Giuseppe; Barbone, Antonella; Giovannico, Lorenzo; Palma, Giuseppe; Mazzone, Federica; Di Bari, Nicola; Parigino, Domenico; Savino, Luca; Di Gioia, Ludovico; Caruso, Irene; Maria Silva, Aline; Milano, Aldo Domenico; et al. (Frontiers in Endocrinology, 2025)
We report a clinical case of multifactorial shock and primary adrenal insufficiency (PAI), caused by bilateral adrenal hemorrhage in the context of catastrophic antiphospholipid syndrome (CAPS) triggered by a COVID-19 infection. A 54-year-old woman was admitted with cardiogenic shock, presenting with severe cardiac dysfunction, neurological alterations, and systemic embolism. Despite initial treatment for suspected septic shock, her condition deteriorated, with bilateral adrenal hemorrhages, markedly elevated adrenocorticotropic hormone (ACTH) levels, low cortisol, and positive antiphospholipid antibodies, leading to the diagnosis of PAI. A multidisciplinary approach, including endocrinology and cardiology expertise, enabled the prompt initiation of hydrocortisone and anticoagulant therapy, which significantly improved her hemodynamic stability and overall clinical status. At follow-up, partial recovery of left ventricular function was observed, although residual cardiac dysfunction persisted. This case highlights the diagnostic challenges associated with CAPS, a rare autoimmune disorder with life-threatening manifestations, including PAI due to adrenal infarction. The overlapping symptoms of CAPS and septic shock often delay diagnosis, underscoring the importance of early recognition of adrenal involvement in patients with CAPS. Furthermore, the patient clinical history, including anticoagulant withdrawal and previous thrombotic events, suggests a need for heightened vigilance in similar cases. In recent years, strong evidence has emerged on the similarities between CAPS and COVID-19, particularly related to the immungenic power of this viral infection and hypercoagulability, but it is also considered that COVID-19 can trigger CAPS. Our findings emphasize the critical role of a coordinated multidisciplinary approach in managing complex CAPS presentations and underline the importance of timely hormone replacement and anticoagulation to improve outcomes in PAI associated with adrenal hemorrhage.